Type 2 diabetes mellitus in pregnancy: The impact of maternal weight and early glycaemic control on outcomes. (February 2019) - Bashir, Mohammed; Dabbous, Zeinab; Baagar, Khaled; Elkhatib, Fadi; Ibrahim, Amin; Brich, Sanam-Alhouda; Abdel-Rahman, Manar E.; Konje, Justin C.; Abou-Samra, Abdul-Badie
Abstract: Objectives: To study the pregnancy outcomes in women with type 2 diabetes mellitus (T2DM) and to relate these to maternal risk factors. Methods: We conducted a retrospective study of 419 women with T2DM (index group)- who attended our diabetes in pregnancy clinic at the Hamad Women's Hospital, Doha, between March 2015 and December 2016 -and 1419 normoglycaemic women (control group). Results: Compared with the controls, T2DM women were older (mean age 34.7 ± 6.9 vs 29.6 ± 5.5 years; p < 0.001) and had a higher BMI (34.5 ± 6.7 vs 28.8 ± 6.1 kg/m2; p < 0.001). The incidence of macrosomia, shoulder dystocia and stillbirth were similar in the two groups, while that of pre-term labour, pre-eclampsia, caesarean section (CS), large for gestational age (LGA), neonatal ICU (NICU) admission, and neonatal hypoglycaemia were significantly higher in the T2DM compared to the control group (p < 0.05). Multivariate regression analysis showed that first trimester HbA1C was associated with an increased risk of LGA (OR 1.17; 95% CI [1.01–1.36]), pre-eclampsia (OR 1.26; 95% CI [1.02–1.54]), neonatal hypoglycaemia (OR 1.32; 95% CI 1.10–1.60) and NICU admission (OR 1.32; 95% CI 1.10–1.60). Pre-pregnancy BMI was associated with increased risk of LGA (OR 1.04; 95%CI [1.00–1.08]), macrosomia (OR 1.06; 95%CI [1.00–1.12]) and CS (OR 1.05; 95% CI [1.01–1.09]). Last trimester HbA1c was associated with an increased risk of LGA [OR 1.53, 95% CI [1.13–2.10)] and CS (OR 1.37, 95% CI [1.01–1.87]). Conclusion: T2DM is associated with adverse pregnancy outcomes compared to the normal control in Qatar. Maternal obesity and glycaemic control before and during pregnancy are the main determinants of pregnancy outcomes in women with T2DM.